The order of genocide : race, power, and war in Rwanda - Straus, Scott, 1970- (Cornell University Press, 2006)
Challenging prevailing studies of the Rwandan genocide, the author provides evidence about local patterns of violence, using original research - including comprehensive surveys undertaken among convicted perpetrators - to assess competing theories about the causes and dynamics of the genocide. Existing interpretations stress three main causes for the genocide: ethnic identity, ideology, and mass-media indoctrination (in particular the influence of hate radio). The author's research does not deny the importance of ethnicity, but he finds that it operated more as a background condition. Instead, the author emphasizes fear and intra-ethnic intimidation as the primary drivers of the violence. A defensive civil war and the assassination of a president created a feeling of acute insecurity. Rwanda's unusually effective state was also central, as was the country's geography and population density, which limited the number of exit options for both victims and perpetrators. In conclusion, the author steps back from the particulars of the Rwandan genocide to offer a dynamic model for understanding other instances of genocide in recent history - the Holocaust, Armenia, Cambodia, the Balkans - and assessing the future likelihood of such events.--adapted from jacket description.